Digital Product Passport as a Carrier of Quality and Provenance Data: Standards, Verification, Monetization Mechanisms, and Consumer Trust - Maksimchuk, Olga (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2023)
This study examines the Digital Product Passport (DPP) as a system-forming technological element that enables the practical implementation of the transition to a circular economy. The analysis focuses on the regulatory, legal, and standardization foundations for DPP deployment, including the European Commission’s proposal of 30 March 2022 for the Ecodesign for Sustainable Products Regulation (COM (2022) 142 final), as well as Regulation (EU) 2023/1542 on batteries and waste batteries, which established the sectoral battery passport as the first formally codified industry precedent. The discussion further covers GS1 specifications and contemporary approaches to cryptographic data verification that support verifiability and immutability of key product information. On this basis, the functional role of the DPP is articulated in strengthening transparency across global supply chains, where traceability, comparability, and information integrity operate as critical conditions for sustainable resource governance and reduced environmental burden. A substantial emphasis is placed on the transformation of Fresh chains-supply chains for perishable products-using an authorial methodology. It is shown that integrating dynamic quality parameters into decision-making loops-from storage and transportation to distribution and retail-creates preconditions for a fundamental reduction in food waste through tighter alignment of logistics operations with the product’s actual condition. At the same time, the study considers the economic logic of lifecycle monetization, analyzing a shift of the analytical center from customer lifetime value (CLV) to product lifetime value (PLV). This shift enables a re-structuring of value assessment with explicit consideration of reuse, repair, recycling, and secondary markets. The argumentation is supported by current statistical evidence on consumer trust, including the HX TrustID™ index, as well as data reflecting willingness to pay a price premium for confirmed, verified sustainability attributes. As a practice-oriented outcome, an architectural model of a decentralized DPP is proposed, combining blockchain infrastructure, decentralized identifiers (DIDs), and verifiable credentials (VCs). Together, these components form a technological contour for reliable provenance attribution, lifecycle event recording, and reproducible verification of declared product characteristics.